The role of glomalin in soil erosion - Vaidya, Geeta Shrestha; Rillig, MC; Wallander, H (Scientific World, 2011)
Glomalin is a glycoprotein, a sugar protein compound that might trigger the formation of soil. In this study we analyze the different organic matters which inhance mycorrhizal fungi and produce glomalin which is dependent upon the types of organic matter. The more glomalin in a particular soil, the soil probably is better. The amount of glomalin in the soil increased as a degree of interdependence increased between plants and arbuscular mycorrhizal fungi. These fungi produce glomalin and live inside plant roots and in the surrounding soil. Growth of Arbuscular mycorrhizal fungi under field conditions was estimated within growth mesh bags which contain different organic matter. After six months these mesh bags were harvested. These soil were analysed in Montana University, USA by two detection methods utilized to quantify Glomalin related soil protein (GRSP): Bradford protein assay, yielding Bradford reactive soil protein (BRSP), and an enzyme-linked immunosorbent assay (ELISA: using the monoclonal antibody Mab32B11 developed against crushed spores of Glomus intraradices,yielding the immunoreactive soil protein. The amount of GRSP in the mesh bags was positively related to organic matter addition. Furthermore, GRSP content was positively correlated to NLFA 16:1ù5 as well as to PLFA 16:1ù5 and bacterial PLFAs .In contrast no correlation was found between spore number and neither fatty acids nor GRSP. Key words : Organic matters; Arbuscular mycorrhizal fungi; Glomalin; Climate change; Green house gas. DOI: http://dx.doi.org/10.3126/sw.v9i9.5524 SW 2011; 9(9): 82-85